ANALYSIS OF BANANA SALE MARKETING IN PANTON LABU DISTRICT, NORTH ACEH - Supristiwendi; Muhammad Jamil; Silvia Anzhita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Bananas are a horticultural commodity that has quite promising potential in business, the relatively large volume of national banana production proves that bananas are the main horticultural product. Pisang sale is a traditional food that is very popular among the people of Aceh, in particular, the most production of banana sale comes from the North Aceh region. The smoking method using firewood and coconut shells is a traditional sale banana processing process. The aim of this research is to analyze marketing and marketing efficiency of banana sale in Panton Labu District, North Aceh. Research using survey method. The samples of craftsmen were 30 people, village traders were 5 people and retailers were 25 people. The results of marketing research on sale bananas in Panton Labu District only use 2 marketing channels. The average marketing cost for selling bananas in Panton Labu District is Rp.3,200/Kg in channel I and Rp.1,500/Kg in channel II. The average marketing margin for selling bananas on channel I is IDR 13,000/Kg, channel II is IDR 9,000/Kg. The average farmer's share in selling banana marketing on channel I was 62.8% and channel II was RP.74.29%. Marketing of sale bananas in Panton Labu District on channel I resulted in an EP value of 9.14% and it was concluded that marketing of sale bananas on channel II was said to be inefficient because the EP value was above 5%. Marketing of sale bananas in Panton Labu District on channel II resulted in an EP value of 4.29% and it was concluded that marketing of sale bananas on channel II was said to be efficient because the EP value was below 5%.